Asas asas perbankan Islam dan lembaga-lembaga terkait (BMUI & Tafakul) di Indonesia - Warkum Sumitro (Raja Grafindo Persada, 1996)
wk,c.1-12/tr,c.13/tr,c.14/tr,c.15/tr,c.16/tr,c.17/ir,c.18-19/tr,c.20/tr,c.21/oen, c.22